Alzheimer’s and Type 2 Diabetes Treatment via Common Enzyme Targeting - R. Jabir, Nasimudeen; A. Kamal, Mohammad; Mohammad Abuzenadah, Adel; Hua Gan, Siew; Nabil Alama, Mohammed; S. Baeesa, Saleh; Tabrez, Shams (CNS & Neurological Disorders - Drug Targets, 2014)
Alzheimer's disease (AD) and type 2 diabetes mellitus (T2DM) are two devastating diseases that are currently incurable. Epidemiological, clinical and pathological evidence has confirmed the co-existence of these two disorders. Moreover, there has been promising progress made in the identification of the pathological linkage between T2DM and AD in the last decade. Hence, developing common treatment strategies for these diseases is important. Currently, enzyme targeting is a potential strategy to cure many diseases. In this communication, we tried to summarize the single enzymetargeted therapeutic approach for the treatment of AD and T2DM. This field of research continues to be active and progressive in identifying many promising enzymes that are involved in both diseases. Based on this review article, we also believe that enzyme inhibition is a promising and reliable strategy for the treatment of many incurable diseases. In the future, we expect that the scientific community will be able to develop common enzyme inhibitors for the treatment of both AD and T2DM.
Keywords: drug therapy